1997
DOI: 10.1006/jcat.1997.1489
|View full text |Cite
|
Sign up to set email alerts
|

Graphite-Supported Platinum Catalysts: Effects of Gas and Aqueous Phase Treatments

Abstract: The effects on the platinum particle diameter and the available platinum surface area of a graphite-supported platinum catalyst resulting from pretreatments and from performing a selective oxidation reaction are investigated. In the gas phase considerable catalyst sintering occurs only in the presence of oxygen at 773 K due to extensive carbon burn-off, whereas in an aqueous phase platinum particle growth is limited upon oxidative treatment. A hydrogen treatment in aqueous phase at 363 K causes platinum partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Thereafter the electrode tip was put in a light sheltered dryer under N 2 -atmosphere. Due to the hydrophilic nature of the oxidised GC reproducible smooth catalyst layers could be produced without the usage of any additives, furthermore the oxidation also enhances the sticking of the silver particles onto the GC [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter the electrode tip was put in a light sheltered dryer under N 2 -atmosphere. Due to the hydrophilic nature of the oxidised GC reproducible smooth catalyst layers could be produced without the usage of any additives, furthermore the oxidation also enhances the sticking of the silver particles onto the GC [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that for platinum supported on graphite at high pH, under a hydrogen-rich atmosphere and at an elevated temperature, agglomeration of platinum could occur. [80] The reason was that removal of the graphite oxygen functional groups by hydrogen lead to lower adhesion and therefore higher mobility of the nanoparticles on the surface.…”
Section: Improving Catalyst Stability By Process Designmentioning
confidence: 99%
“…[6][7][8][9][10] increases catalyst particle size, reducing available electrochemical surface area (ECSA in m 2 g −1 cat ) and therefore should increase voltage loss (due to an increase in oxygen reduction overpotential). Furthermore, Pt dissolution or particle growth have been shown to be a function of potential [11,12], fuel cell operating temperature [7,8], relative humidity [7], and the presence of water [13][14][15][16], making it difficult to theoretically predict the resulting ECSA change over time in various Pt alloy systems. For Pt alloy nanoparticle catalysts, the issue of stability has often been convoluted due to the cross-comparison of alloys with various preparation conditions or particle size.…”
Section: Introductionmentioning
confidence: 99%